The genome of Schmidtea mediterranea and the evolution of core cellular mechanisms - Grohme, Markus Alexander; Schloißnig, Siegfried; Pippel, Martin; Powell, Sean (Nature, 2018)
The planarian Schmidtea mediterranea is an important model for stem cell research and regeneration, but adequate genome resources for this species have been lacking. Here we report a highly contiguous genome assembly of S. mediterranea, using long-read sequencing and a de novo assembler (MARVEL) enhanced for low-complexity reads. The S. mediterranea genome is highly polymorphic and repetitive, and harbours a novel class of giant retroelements. Furthermore, the genome assembly lacks a number of highly conserved genes, including critical components of the mitotic spindle assembly checkpoint, but planarians maintain checkpoint function. Our genome assembly provides a key model system resource that will be useful for studying regeneration and the evolutionary plasticity of core cell biological mechanisms.